Short Breast Health Perception Questionnaire: Turkish validity and reliability study - Karaman, Seda; Turan, Gülcan Bahçecioğlu; Özer, Zülfünaz (My University, 2025)
Aim: The aim of the present study was to examine the Turkish validity and reliability of the Short Breast Health Perception Questionnaire in women. Method: A total of 400 women who were admitted to the Internal Medicine polyclinics of Fırat University Hospital were included in this methodological study. After the translation process of the questionnaire, content and construct validity were conducted. Explanatory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted for construct validity, while item analyses and internal consistency analysis were conducted for reliability. Results: It Total variance rate explained in the explanatory factor analysis found as a result of the evaluations and analyses was 66.35%. Factor loads of all items in the study ranged between 0.69 and 0.88. The questionnaire had a Cronbach’s alpha value of 0.940. EFA and CFA showed that the Turkish version of the 11-item and one-factor Short Breast Health Perception Questionnaire was confirmed without any changes to the original scale form. CFA results showed good fit index values. Conclusion: Short Breast Health Perception Questionnaire Turkish version is a valid and reliable measurement instrument for evaluating women’s perception of breast health and for use in clinical practice.
Keywords: Validity; reliability; scale; breast cancer; woman